Still a long way to go: decomposing income inequality across Italy's regions, 1871 – 2011 - Gabriele Cappelli; Emanuele Felice; Julio Martínez-Galarraga; Daniel Tirado (European Historical Economics Society (EHES), 2018)
This article is the first study to explore to what extent labour productivity, structural change, participation rates and the age structure of the population contributed to the pattern of Italy's regional economic inequality over the long run (1871-2011). We provide brand new regional estimates of participation rates and age structures, as well as the most updated figures on per capita GDP, per worker GDP and the employment rate (at ten-year intervals spanning from 1871 to 2011). First, regional inequality in per capita GDP (Y/N) is split into labour productivity (Y/L) and labour-market features (L/N). Then, the Caselli-Tenreyro decomposition is used to explore whether labour-productivity convergence (or divergence) at the NUTS-1 level was determined within or between sectors, and by labour reallocation. While labour productivity was central to the pattern of Italy's regional development until the 1970s, since then the key factor of North-South divergence has been the participation rate. The results confirm the central role of national and local policies, influencing per capita GDP via productivity, employment, and participation rates.
Keywords: R1; O11; O25; N9; 330; Regional disparities; Italy; convergence; divergence; Caselli-Tenreyro; economic history; productivity